2014
DOI: 10.1586/14760584.2015.956729
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-based vaccine adjuvants: incomplete characterization complicates preclinical and clinical evaluation

Abstract: A number of preclinical and clinical studies with chitosan-adjuvanted antigen- and DNA-based vaccines have been carried out. Various chitosans and their modifications, in different forms (solutions, powders, gels and particles), have been evaluated with various antigens administered via different routes. Chitosan is a generic name for a wide array of glucosamine-based substances derived from biological sources, and standardization is necessary. However, in most of the studies published to date, molecular weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 77 publications
0
47
0
3
Order By: Relevance
“…Proposed mechanisms underlying the adjuvanticity of chitosan include antigen protection, depot formation, enhanced antigen uptake and presentation and direct modulation of immune responses (Vasiliev, 2015). Another plausible suggestion is that chitosan-induced cell death might promote the release of DAMPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed mechanisms underlying the adjuvanticity of chitosan include antigen protection, depot formation, enhanced antigen uptake and presentation and direct modulation of immune responses (Vasiliev, 2015). Another plausible suggestion is that chitosan-induced cell death might promote the release of DAMPs.…”
Section: Discussionmentioning
confidence: 99%
“…However, a major disadvantage of alum is its limited ability to efficiently drive T helper 1 (Th1) responses. The chitin derivative chitosan is an attractive alternative to alum, being biocompatible, flexible in terms of formulation and degree of deacetylation, and efficacious when administered mucosally (Vasiliev, 2015). We found that chitosan is superior to alum in promoting Th1 responses (Mori et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Key characteristics, such as chitosan’s molecular weight, degree of deacetylation, viscosity, and endotoxin levels [93], should be considered when testing chitosan for adjuvant applications. It would be helpful to refer Vasiliev’s (2015) step-by-step approaches in the proper evaluation and standardization of chitosan for use as vaccine-adjuvants [94]. …”
Section: Chitosan In Cancer Immunotherapymentioning
confidence: 99%
“…Chitosan, as a cationic polysaccharide bearing lots of reactive groups, possesses beneficial properties for vaccine formulation, including biocompatibility, flexibility in terms of formulation and degree of deacetylation, and efficacy when administered via mucosal route, and ability to promote immune responses [41,42], and thus is thought a superior alternative to alum which only favors promoting humoral responses [43]. Also, chitosan is thought suitable for constituting a mucosal VADS thanks to its bio-adhesive character and intrinsic adjuvanticity, which may arise from chitosan-mediated inflammasome activation [44], or from triggering certain type of PRRs such as TLR4 on immune cells [45], in consistence with its parent molecule chitin which is confirmed able to activate immunocytes via binding to mannose receptors and TLR2 to initiate innate immune responses [46].…”
Section: Chitosan Npsmentioning
confidence: 99%